Effects of lubricant oil on particulate emissions from port-fuel and direct-injection spark-ignition engines. (August 2017) - Amirante, Riccardo; Distaso, Elia; Napolitano, Michele; Tamburrano, Paolo; Di Iorio, Silvana; Sementa, Paolo; Vaglieco, Bianca Maria; Reitz, Rolf D
This work presents experimental tests where lubricant oil was added to the engine in order to highlight its contribution to particle emissions from both gasoline and compressed natural gas spark-ignition engines. Three different ways of feeding the extra lubricant oil and two fuel-injection modes—port fuel injection and direct injection—were investigated to mimic the different ways by which lubricant may reach the combustion chamber. In particular, in the tests using compressed natural gas, the oil was injected either into the intake manifold or directly into the combustion chamber, whereas in both the port-fuel-injection and direct-injection tests using gasoline, the oil was premixed with the fuel. The experiments were performed on a single-cylinder, optically accessible spark-ignition engine, running at 2000 r/min under stoichiometric and full-load conditions, and requiring no lubrication. Particle size distribution functions were measured in the range from 5.6 to 560 nm by means of an engine exhaust particle sizer. Particle samples were taken directly from the exhaust flow, just downstream of the valves. Opacity was measured by an AVL 439 opacimeter, and gaseous emissions were measured by means of an exhaust gas analyzer in order to globally monitor the combustion process. Detailed analysis of the recorded total particulate number and particle size distributions allowed to determine the size ranges and relative amounts associated with the lubricant-oil-derived particles. Oil addition produced a significant increase in the particles emitted in the lowest range size, independent of the way lubricant was added. Only when lubricant was injected directly into the combustion chamber (either blended with the fuel or by itself), an increase in the number of particles with sizes larger than 50 nm was recorded.